2014
DOI: 10.3109/14992027.2014.888597
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicity effects of low exposure to solvent mixture among paint manufacturing workers

Abstract: Although solvent mixture concentrations and noise levels were low, our results demonstrate that there may be a concurrent ototoxicity and neurotoxicity condition and emphasize the importance of including BAEP analysis for comprehensive assessments. Future studies that include otoacoustic emissions assessments to monitor cochlear function and central auditory processing tests are imperative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
2
14
0
3
Order By: Relevance
“…Therefore, the ABR findings obtained in the present study suggest that the workers exposed to gasoline have auditory nerve dysfunction, as well as central auditory nervous system dysfunction involving brainstem. Dysfunction involving the auditory pathway in brainstem was also reported in a study of gasoline station workers as well as in workers exposed to solvents (Abbate et al 1993;Vrca et al 1996;Prasher et al 2005;Gopal 2008;Ju arez-P erez et al 2014;Fuente, McPherson and Cardemil 2013).…”
Section: Auditory-evoked Potentialsmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, the ABR findings obtained in the present study suggest that the workers exposed to gasoline have auditory nerve dysfunction, as well as central auditory nervous system dysfunction involving brainstem. Dysfunction involving the auditory pathway in brainstem was also reported in a study of gasoline station workers as well as in workers exposed to solvents (Abbate et al 1993;Vrca et al 1996;Prasher et al 2005;Gopal 2008;Ju arez-P erez et al 2014;Fuente, McPherson and Cardemil 2013).…”
Section: Auditory-evoked Potentialsmentioning
confidence: 61%
“…Significantly longer ABR latencies for workers exposed to solvents have been observed (Abbate et al 1993;Vrca et al 1996;Fuente, McPherson, and Cardemil 2013;Ju arez-P erez et al 2014) but not always for the same waves. The mean latencies of waves I, III and V (Abbate et al 1993;Vrca et al 1996), I-III, III-V and I-V IPL (Abbate et al 1993), and III-IV IPL (Vrca et al 1996) were significantly longer for the exposed group than for the CG.…”
Section: Auditory-evoked Potentialsmentioning
confidence: 82%
“…[2] Although solvent mixture concentrations and noise levels were low, a study was demonstrated that there might be a concurrent ototoxicity and neurotoxicity condition. [26] In contrast, Sliwinska-Kowalska et al demonstrated that workers exposed to solvents at moderate concentrations had a raised risk of hearing impairment, but found no relationship between hearing impairment and the concentrations of the solvent. [27] The inconsistency between studies may be caused by the type and concentration of the solvent or mixture under study.…”
Section: Discussionmentioning
confidence: 90%
“…The human auditory system is vulnerable to the toxic effects of some VOCs, even at concentrations below recommended occupational exposure limits (OELs) (Juárez-Pérez et al 2014;Morata et al 2002). One reason for this may be because ototoxicity is rarely cited in the determination of the American Conference of Governmental Industrial Hygienists (ACGIH) occupational exposure limit (OEL); currently this is so for only one VOC, ethylbenzene (ACGIH 2017).…”
Section: Introductionmentioning
confidence: 99%